1981
DOI: 10.1172/jci110010
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte-mediated Serum-independent Damage to Hyphal and Pseudohyphal Forms of Candida albicans In Vitro

Abstract: A B S T R A C T Human peripheral blood monocytes attached to Candida albicans hyphae in the absence of serum and damaged the hyphae without completely ingesting them. Attachment and damage was not augmented by the addition of serum. Damage to hyphae was quantitated by a previously developed metabolic assay that measured leukocyte-induced reduction in uptake of [14C]cytosine by the hyphae. Use of cells from patients with hereditary disorders of leukocyte function, chronic granulomatous disease, and myeloperoxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
1

Year Published

1982
1982
2001
2001

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 33 publications
2
23
1
Order By: Relevance
“…In contrast, murine FSDC do produce NO upon phagocytosis of Candida and hyphae, but no definitive evidence was presented to demonstrate that NO actually was responsible for killing the Candida cells (19). As our immature DC were derived from peripheral blood monocytes, these data fit in with the general idea that the preponderance of human neutrophil candidacidal activity is mediated via the production of toxic oxygen metabolites (16,77,81), whereas killing of Candida by human monocytes and M occurs predominantly though nonoxidative mechanisms (17,44,77).…”
Section: Discussionsupporting
confidence: 75%
“…In contrast, murine FSDC do produce NO upon phagocytosis of Candida and hyphae, but no definitive evidence was presented to demonstrate that NO actually was responsible for killing the Candida cells (19). As our immature DC were derived from peripheral blood monocytes, these data fit in with the general idea that the preponderance of human neutrophil candidacidal activity is mediated via the production of toxic oxygen metabolites (16,77,81), whereas killing of Candida by human monocytes and M occurs predominantly though nonoxidative mechanisms (17,44,77).…”
Section: Discussionsupporting
confidence: 75%
“…These authors have shown that significant anti-hyphal activity is exerted by lymph node cells pre-exposed in vitro to IL-2 and conclude that the active effector cell is functionally and phenotypically similar to an activated NK cell. While previous reports (Diamond et al, 1978(Diamond et al, , 1981Baccarini et al, 1985;Scaringi et al, 1991) have shown that hyphae can be damaged by PMN cells and monocytes, our data together with those of Beno & Mathews (1 990) indicate that non-phagocytic effector cells can also exert anti-hyphal activity.…”
Section: Discussionsupporting
confidence: 49%
“…Indeed, MPO-deficient granulocytes successfully destroyed both erythrocyte3 and endothelial cell targets (23). Recent reports have also demonstrated that human monocytes and neutrophils can destroy target cells in antibody dependent (14,(50)(51)(52) or serum independent systems (53 …”
Section: Discussionmentioning
confidence: 99%